Results account as a source of economic information = Rachunek wyników jako źródło informacji ekonomicznych - Nowak, Edward (Zielona Góra: Faculty of Economics and Management Press)
Financial result is one of the fundamental economic categories subject to measurement within the accounting system. Financial result is a complex economic category, since its fluctuations are determined by expenses and revenues. The volume of financial results is related to activities in each of the individual areas of business operation and to selected external factors.
Keywords: rachunek wyników; informacje ekonomiczne; sprawozdawczość finansowa; zarządzanie wynikami; results account; economic information; financial reporting; results management